Handbook of Infrared Standards II : with spectral coverage of 1.4 [mu]m-4 [mu]m and 6.2 [mu]m-7.7 [mu]m - Guelachvili, Guy (Elsevier Science, 1993)
This timely compilation of infrared standards has been developed for use by infrared researchers in chemistry, physics, engineering, astrophysics, and laser and atmospheric sciences. Providing maps of closely spaced molecular spectra along with their measured wavenumbers between 1.4vm and 4vm, this handbook will complement the 1986 Handbook of Infrared Standards that included special coverage between 3 and 2600vm. It will serve as a necessary reference for all researchers conducting spectroscopic investigations in the near-infrared region.